Activation of the VpdmVGLUT1-VPM pathway contributes to anxiety-like behaviors induced by malocclusion - Ji, Yuan-Yuan; Liu, Xin; Li, Xin; Xiao, Yi-Fan; Ma, Teng; Wang, Jian; Feng, Yue; Shi, Juan; Wang, Mei-Qing; Li, Jin-Lian; Lai, Jiang-Hua (Frontiers in Cellular Neuroscience, 2022)
Occlusal disharmony has a negative impact on emotion. The mesencephalic trigeminal nucleus (Vme) neurons are the primary afferent nuclei that convey proprioceptive information from proprioceptors and low-threshold mechanoreceptors in the periodontal ligament and jaw muscles in the cranio-oro-facial regions. The dorsomedial part of the principal sensory trigeminal nucleus (Vpdm) and the ventral posteromedial nucleus (VPM) of thalamus have been proven to be crucial relay stations in ascending pathway of proprioception. The VPM sends numerous projections to primary somatosensory areas (SI), which modulate emotion processing. In this study, the Vpdm was taken as the input nucleus to investigate the modulation of VPM neurons during malocclusion-induced negative emotion in mice. Retrograde-tract tracing and chemogenetic and optogenetic approaches were used to examine the role of the Vme-Vpdm-VPM-SI pathway in aforesaid negative emotion. First, morphological evidence of the involvement of the Vme-Vpdm-VPM pathway, Vpdm-VPM-SI pathway and VpdmVGLUT1-VPM pathway in orofacial proprioception was investigated in wild-type mice and vesicular glutamate transporter 1 (VGLUT1)::tdTomato mice. Furthermore, chemogenetic inhibition of VpdmVGLUT1 neurons and the Vpdm-VPM pathway alleviated anxiety-like behaviors in a unilateral anterior crossbite (UAC) model, whereas chemogenetic activation induced anxiety-like behaviors in controls and did not aggravate these behaviors in UAC mice. Finally, optogenetic inhibition of the VpdmVGLUT1-VPM pathway in VGLUT1-IRES-Cre mice reversed UAC-induced anxiety comorbidity. In conclusion, these results suggest that the VpdmVGLUT1-VPM neural pathway participates in the modulation of malocclusion-induced anxiety comorbidity. These findings provide new insights into the links between occlusion and emotion and deepen our understanding of the impact of occlusal disharmony on brain dysfunction.